Science, Metaphoric Meaning, and Indigenous Knowledge - Elliott, Frank (Alberta Journal of Educational Research, 2010)
Western cultural approaches to teaching science have excluded Indigenous knowledges and culturally favored many non-Aboriginal science students. By asking the question “What connections exist between Western science and Indigenous knowledge?” elements of epistemological (how do we determine what is real?) and ontological (what is real?) connections can emerge for science educators. Western science as it is presented in Alberta classrooms is characterized as teaching scientism by the degree to which it excludes the presentation of other ways of knowing. The objectivity of Western science is questioned here, and aspects of Indigenous knowledge are suggested that coincide with and can support science teaching. The concept of indeterminacy and flux as suggested by Bohm (1980), Little Bear (2004), and Peat (2002) form a nexus where Western scientific epistemologies and ontologisms are congruent with Indigenous knowledge. Metaphoric meaning is suggested as one useful area of congruence for science education praxis.